La publicación editorial como motor para el desarrollo de la inteligencia emocional infantil: Mi Súper KIT Emocional (2023)
The term Emotional Intelligence (EI) can be confusing and complicated, especially when we aim to apply it in early childhood. This undergraduate project’s objective is to design a pathway that facilitates the integration of EI with a group of children or with an individual child. It is important to note that all the materials included in the KIT resulting from this undergraduate project serve as the initial step toward fostering emotional intelligence. It is intended for children aged 5 to 7 years old, with the guidance of a reading mediator.